Regulation of the yeast DNA replication genes through the Mlu I cell cycle box is dependent on SWI6. - Verma, R (1992)
In Saccharomyces cerevisiae, at least 17 DNA replication genes are coordinately expressed at the G1/S boundary during the cell cycle. All of these genes have the DNA sequence element ACGCGT in their 5' upstream regulatory regions. This sequence has been shown to be essential for periodic expression of the POL1, CDC9, and TMP1 genes. The cyclin (CLN1 and CLN2) and HO genes are another subset of genes that are expressed with the same timing as the DNA replication genes. Their periodic expression requires the participation of two well-characterized transcriptional activators: the SWI4 and SWI6 gene products. In this study, we present evidence that SWI6 contributes to the regulation of DNA replication genes as well. Surprisingly, a preferential requirement for SWI6 over SWI4 is observed in our studies of ACGCGT-dependent reporter gene expression in vivo. This selectivity has not been observed for the other G1/S genes. Correlating with the in vivo results, protein-DNA complexes formed in vitro on multimeric ACGCGT elements are either abolished or reduced in swi6 delta deletion mutants.